Growth, Yield-Related Traits and Yield of Lowland Maize (Zea mays L.) Varieties as Influenced by Inorganic NPS and N Fertilizer Rates at Babile, Eastern Ethiopia - Mekuannet K. Belay (International Journal of Agronomy)
Appropriate selection of varieties based on agroecologies and application of the right amount and type of fertilizers based on crop requirements are crucially indispensable to maximize maize production. A field experiment was conducted for two consecutive years under main cropping seasons to evaluate the effect of blended NPS and N fertilizer rates on growth, yield components, and yield of open-pollinated maize varieties at the moisture stress area, eastern Ethiopia. The experiment was comprised of two lowland maize varieties, three blended NPS (50, 100, and 150 kg), and three N levels (43.5, 87, and 130.5 kg) ha−1 using a factorial arrangement under a randomized complete block design with three replications. The results showed that the leaf area index, thousand kernel weight, and biomass and grain yields were significantly influenced by the interaction effect of variety × NPS and N in the first growing season. The number of ears per plant, ear length, ear diameter, number of kernels per ear, and biomass yield were significantly affected due to variety in the second growing season. The maximum growth parameters and yield components were recorded from Baate and 150 kg blended NPS. Grain yield and harvest index were statistically affected by interaction effects of variety × NPS and N in both years. Therefore, the highest grain yield (9.7 t·ha−1) was produced from Baate at a combined application of 150 kg NPS and 130.5 kg N·ha−1. The partial budget analysis also confirmed that the highest net benefit (2,033.4 USD) with the highest marginal rate of return (3106.9%) was obtained at Baate variety where plants were fertilized with 150 NPS and 130.5 kg N·ha−1. In conclusion, an integrated application of 150 NPS + 130.5 kg N·ha−1 to Baate variety is agronomically optimum and economically realistic fertilizer level to get a higher grain yield in the study area.